Influence of Thermal Modification of Beech on the Strength of Longitudinally Connected Turned Elements by Rotational Welding Method - Ivica Župčić (University of Zagreb, Faculty of Forestry and Wood Technology, 2011)
Wood welding technique is a newer way of connecting wooden parts without using glue with the temperature usually achieved by friction of elements that are connected. During the welding process, due to the influence of pressure and temperature, the surface wood layer (lignin and polyoses) is melted. The research is based on an examination of the influence of thermal modification and the impact of water (room temperature) on the strength of welded joints. Test samples were longitudinally connected turned elements made of solid beech wood. Thermally modified wood can be successfully welded. The results showed that increasing the temperature of thermal modifi cation and immersing the samples in cold water (20 °C) cause the decrease of embedded force and tensile strength, respectively. The research has also shown that the increase in weight loss during thermal modification reduces the tensile forces. With samples immersed in cold water, the highest joint strength was recorded in welding thermally modified wood at 140 °C and the lowest joint strength was recorded in welding thermally modified wood at 180 °C.